Психологические особенности мотивации профессионального развития педагога в педагогической деятельности - Эшмуродова Ширин Ойбек кизи (Academia One, 2026)
The role of educators in educating future specialists to be well-rounded and well-rounded, deeply educated, and highly spiritual is incomparable. The professional development of a teacher plays a leading role in achieving educational effectiveness. For this reason, it is extremely important to study the psychological characteristics of the motivation for the professional development of a teacher in pedagogical activity
Keywords: Teacher; specialist; qualitative motivation